Strategi Pemasaran Wardah Di Indonesia - Ilham Ansori Hasibuan; Muhammad Zen; Fatmawati (Journal of Management Specialists, 2024)
This research aims to analyze and evaluate the marketing strategies implemented by the Wardah cosmetics brand in Indonesia. Through a qualitative approach, data was collected through interviews with Wardah management, market observations, and analysis of related documents. The findings show that Wardah has successfully implemented a marketing strategy that focuses on appropriate market segmentation, the use of social media and influencer marketing, as well as consistent product quality. By understanding Indonesian consumer preferences and utilizing digital platforms effectively, Wardah is able to strengthen its brand image and maintain its position as one of the market leaders in the halal beauty industry in Indonesia. The implications of this research provide valuable insights for other brands in similar industries as well as contribute to further understanding of marketing strategies in the Indonesian cosmetics market.